2021
DOI: 10.1007/s42380-021-00088-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Ethnicity of Victims and Bullies Really Matter? Suggestions for Further Research on Intra-Ethnic Bullying/Victimisation

Abstract: This review aims to address a growing concern: Why are ethnic minority students, such as of Roma, bullied by their in-group peers for an ethnical reason? According to recent findings, intra-ethnic bullying is becoming more prevalent across Europe; ethnic minority students are often bullied by one another more than by White-European peers. However, less is known about how intra-ethnic bullying happens in the same-or cross-ethnic minority groups and how it differs from inter-ethnic bullying. How classroom ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Rather, such engagement is due more to what youth bring with them (e.g., attitudes and moral values) to this context. This finding is in fact in line with the current conceptual discussions (Kuldas et al, 2021) and empirical findings presented in previous research, which have shown that Swedish adolescents who hold negative attitudes toward immigrants are likely to harass their ethnic minority peers in ethnically diverse classrooms (Bayram Özdemir et al, 2018). In sum, the findings suggest that heterogenous classroom environments may not directly promote positive inter-ethnic interactions or lead to ethnic conflicts among youth.…”
Section: Discussionsupporting
confidence: 91%
“…Rather, such engagement is due more to what youth bring with them (e.g., attitudes and moral values) to this context. This finding is in fact in line with the current conceptual discussions (Kuldas et al, 2021) and empirical findings presented in previous research, which have shown that Swedish adolescents who hold negative attitudes toward immigrants are likely to harass their ethnic minority peers in ethnically diverse classrooms (Bayram Özdemir et al, 2018). In sum, the findings suggest that heterogenous classroom environments may not directly promote positive inter-ethnic interactions or lead to ethnic conflicts among youth.…”
Section: Discussionsupporting
confidence: 91%
“…It is, therefore, unclear if the association between bullying and SITBs could be generalized across sociodemographic groups. There may be specific nuances faced within or between people of different ethnicities (Kuldas et al, 2021 ), with victimization greater among poorer students (Hosozawa et al, 2021 ). Indeed, current in‐school bullying prevention programs may be less effective in minority ethnic groups, therefore highlighting the importance of understanding the nature of bullying across diverse populations (Limber et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have highlighted that perceived threat of an out-group entity towards the group identity can lead to aggressive behaviour (Gini, 2007). Examples of this behaviour have been reported in the context of school bullying (Gini, 2006;Kuldas et al, 2021;Ojala & Nesdale, 2004) but also in human-robot interactions (Keijsers & Bartneck, 2018;Keijsers et al, 2021). Perceived threat has been also linked to the notion of dehumanisation, particularly in the context of immigrants (Louis et al, 2013;Pavetich & Stathi, 2021;Viki et al, 2013).…”
Section: Hypotheses Development Regarding the Effect Of Personalitymentioning
confidence: 99%